MicroRNA-182-5p Inhibits Hypertrophic Scar Formation by Inhibiting the Proliferation and Migration of Fibroblasts via SMAD4 Pathway - Jin M; Xu X (Clinical, Cosmetic and Investigational Dermatology, 2023)
Mingzhu Jin,1 Xiao Xu2 1Department of Burns and Plastic Surgery, Fourth Medical Center of Chinese PLA General Hospital, Beijing, People’s Republic of China; 2Department of Ophthalmology, Third Medical Center of Chinese PLA General Hospital, Beijing, People’s Republic of ChinaCorrespondence: Xiao Xu, Email 13623345@qq.comIntroduction: Secondary to war wounds, trauma, etc., hypertrophic scar formation is the cause of an excessive proliferation of fibroblasts and accumulation of collagen fibers, which might affect cosmetic appearance, and could cause malignant transformation. miRNAs play an important role in disease regulation via inhibiting post-transcriptional protein translation by targeting and binding to the 3’ UTR region of mRNA. Here we explore the mechanism and interventions of scar formation from the perspective of miRNA.Methods: Hypertrophic scar-associated differential miRNAs were screened by analyzing sequencing data of normal skin and hypertrophic scar, and verified by RT-qPCR. Signaling pathways that may be influenced by differentially miRNAs were analyzed using KEGG and GO. miRNA mimics were used to explore the effects of miRNAs on SMAD signaling pathway proteins. Dual-luciferase assays were used to explore the targeted binding of miRNAs. The mimics of the miRNA were used to explore the impact of miRNAs on the proliferation, migration, apoptosis and collagen synthesis levels of hypertrophic scar fibroblasts. The scar model of rabbit ear was used to verify the influence of miRNA on wound healing and scar formation in vivo.Results: Expression of miR-182-5p was found to be considerably decreased in hypertrophic scars and fibroblasts. miR-182-5p was found to act mainly by targeting the 3’UTR region of SMAD4, but not SMAD1 or SMAD3. miR-182-5p overexpression may drastically suppress the proliferation and migration of fibroblasts, accompanied by enhanced apoptosis and reduced collagen fiber synthesis. The overexpression of miR-182-5p in in vivo experiments could effectively inhibit hypertrophic scar formation without affecting the speed and quality of wound healing.Conclusion: miR-182-5p inhibits hypertrophic scar formation by decreasing the proliferation and migration of fibroblasts via SMAD4 pathway, and is expected to become a novel hypertrophic scar therapeutic target.Keywords: hypertrophic scar, microRNA, SMAD4, fibroblasts